Pre-reading as an aid to making a reading outline - Torrecampo, Rosella Moya-.; Alfonso, Grace Javier 1950-. ([Quezon City] U.P. Open University, 2005)
A guide to building pre-reading skills leading to outline-making and writing.
Published jointly with the Commission on Higher Education.
Executive producer: Maria Lurenda Suplido ; Assistant director: Arminda Santiago ; Associate producer: Mitzi Rivera-Angobung ; Scriptwriters: Rosella Moya-Torrecampo, Maria Ana T. Quimbo and Grace Javier Alfonso.
Narrator: Rosella Moya-Torrecampo, Professor, College of Arts and Letters, U.P. Diliman.
Keywords: Reading; Reading readiness; Reading comprehension -- Study and teaching; Study skills